WORK FOR THE PUBLIC INTEREST IN CRIMINAL SYSTEM PRACTICE IN THE REPUBLIC OF SRPSKA - Vasić, Milijan (Politeia, 2020)
The criminal justice system in the Republic of Srpska exists as an independent legal system within Bosnia and Herzegovina. To date, not much has been done regarding the implementation of public interest work in the case-law. The Criminal Code of the Republic of Srpska, 2017 Edition (CC RS, 2017) prescribes this work as an alternative measure of punishing offenders who are accused and prosecuted to a prison sentence up to one year.Even though Article 70 of the Criminal Code of the Republic of Srpska clearly prescribes work for the public interest, a stronger will is required on the part of the Republic of Srpska legislature to regulate, by means of a by-law  - the Rulebook -  the manner, form, and all other parametres for the implementation of all that is prescribed. Consequently,  this requires a greater  involvement of the Ministry of Justice, as the head of the implementation of this alternative measure in practice provided by law.Work for the public interest, even where legal provisions allow for such practice, is still not prescribed by courts in the Republic of Srpska, since there is no by-law that would determine the manner of implementation of the aforementioned  alternative measure, specify all national authorities with clear responsibilities, and elaborate thoroughly how the work of the public interest should be implemented as a rehabilitative alternative measure. At a press conference in October 2019, the Ministry of Justice of the Republic of  Srpska announced that the Rulebook was in the process of development. That way, in the near future, legally convicted persons in our country would be provided with this measure of re-socialisation. By working for the benefit of the community, in constant interaction with it, a convicted person would endure the imposed sentence, which would enable them to better understand the gravity of their actions and help them return to society as equal members.
Keywords: Work for the public interest; Alternative measures; Criminal offinses; Criminal sanction; Convicted person